Species diversity and distribution of the genus Halimeda J.V. Lamour (Chlorophyta) in Malaysian waters - Tay, Vangene (2022)
Halimeda is a well-known tropical benthic genus of green algae and plays an important ecological role in marine ecosystems. Halimeda species are recognized as a carbon sink due to their ability to capture CO2 for photosynthesis and bicarbonate for calcification. Morphology and anatomy of Halimeda varies among populations of the same species, these high intraspecific polymorphism complicates species identity in Halimeda and causes taxonomic problems. Furthermore, few studies on its taxonomy have been conducted in Malaysian waters despite Halimeda being reported as common in the tropical seas. Species identification has been based mainly on gross morphology: segments shape and size, thallus and holdfast; and anatomy: utricles shapes and size and nodes. Nowadays, species identification is challenging without the assistance of molecular analyses due to the high intraspecific polymorphisms observed. Hence, both morpho-anatomical examination and molecular analyses were undertaken on Malaysian Halimeda species to investigate their biodiversity and distribution. Chloroplast tufA and rbcL markers were used to characterize Halimeda species and update their species diversity status in Malaysia. A total of 62 specimens of Halimeda from Malaysian coastal areas were examined and 15 species were identified: H. borneensis, H. cuneata, H. cylindracea, H. discoidea, H. gigas, H. distorta, H. heteromorpha, H. macroloba, H. macrophysa, H. micronesica, H. minima, H. opuntia, H. taenicola, H. velasquezii and H. xishaensis. Of the 15 recognized morphospecies, we confirmed four species using a molecular approach: H. discoidea, H. gigas, H. macroloba and H. xishaensis. This study added seven new records of marine flora in Malaysia, namely: H. ishaensis, H. gigas, H. minima, H. micronesica, H. cylindracea, H. distorta and H. heteromorpha. H. xishaensis. Distribution studies suggest that the most abundant species were H. opuntia and H. macroloba. In East Malaysia, species diversity was found to be greater in Sabah and Labuan, whereas the west coast of West Malaysia showed greater species diversity as compared to the east coast. The diversity and distribution of Halimeda in Malaysia may have been affected by biogeographic barriers such as Sunda Shelf Barrier (SSB) and Thai-Malay Peninsula; changes in sea surface currents during the southwest and northeast monsoons; and reproductive biology of Halimeda. This study is the first to include molecular analyses to aid species identification of Halimeda in Malaysia. Based on the phylogenetic analyses, tufA is a more suitable marker for species delineation of Halimeda as compared to rbcL. These results may assist future studies on species variation and geographic distribution of Halimeda in Malaysia by utilizing morphological and molecular analysis.